The Role of Using Body Language in Turkish Teaching on Learning and Attitude - (:unkn) unknown (HACETTEPE UNIV, 2015)
In daily life, while we are walking, sitting or even while we are thinking, we give various conscious or unconscious messages with our hands, arms, facial expressions and clothes. These messages reflect people's feelings, thoughts and attitudes towards a person, an object or a topic. The aim of this study is to investigate the effects of the teachers' body language use on the learning levels and attitudes of the students. To that end, open-ended questions were asked to 95 students from the Marmara University, Ataturk Faculty of Education, Turkish Education Department, and their views about the positive and negative effects of the teachers' body language use on the learning levels and attitudes of the students were collected. The study was conducted in the survey model and the answers of the students were evaluated using the content analysis method. At the end of the study, it is found that both students' learning levels and attitudes towards the lessons are substantially affected by the teachers' body language.
Keywords: Turkish education; body language; language education